Influenza Vaccination and the Risk of Ventricular Arrhythmias in Patients With Chronic Obstructive Pulmonary Disease: A Population-Based Longitudinal Study - Chen, Chun-Chao; Lin, Cheng-Hsin; Hao, Wen-Rui; Yeh, Jong-Shiuan; Chiang, Kuang-Hsing; Fang, Yu-Ann; Chiu, Chun-Chih; Yang, Tsung Yeh; Wu, Yu-Wei; Liu, Ju-Chi (Frontiers in Cardiovascular Medicine, 2021)
Backgrounds: Influenza vaccination could decrease the risk of major cardiac events in patients with chronic obstructive pulmonary disease (COPD). However, the vaccine’s effects on decreasing the risk of ventricular arrhythmia (VA) development in such patients remain unclear. Methods: We retrospectively analysed the data of 18,658 patients with COPD (≥55 years old) from the National Health Insurance Research Database during January 1, 2001 to December 31, 2012. After a 1:1 propensity score matching by the year of diagnosis, we divided the patients into vaccinated and unvaccinated groups. Time-varying Cox proportional hazards regression was applied to assess the time to event hazards of influenza vaccination exposure Results: The risk of VA occurrence was significantly lower in the vaccinated group during influenza season and all seasons (adjusted hazard ratio [aHR]: 0.62, 95% confidence interval [CI]: 0.41–0.95; aHR: 0.69, 95% CI: 0.44–1.08; and aHR: 0.65, 95% CI: 0.48–0.89, in influenza season, non-influenza season and all seasons respectively). Among patients with CHA2DS2-VASc scores of 2-3, receiving one time and two to three times of influenza vaccination were associated with lower risk of VA occurrence in all seasons (aHR: 0.28, 95% CI: 0.10–0.80; aHR: 0.27, 95% CI: 0.10–0.68, respectively). Among patients without stroke, peripheral vascular disease and diabetes, lower risk of VA occurrence after receiving one and two to three times of vaccination was observed in all seasons. Among patients with history of asthma and patients without history of heart failure, ischemic heart disease, angina hypertension or renal failure, significantly lower risk of VA occurrence was observed after the first time of vaccination in all seasons. Conclusions: Influenza vaccination may be associated with lower risks of VA among patients with COPD aged 55 to 74. Further investigation is still needed to resolve this clinical question.